COVID-19 Legacy: Post-pandemic Qualitative Meta-Analysis on Students Teacher-Dependency Amongst Master Two Populations in Algeria (Global Journal of Human-Social Science, 2023)
A meta-analytic approach was conducted to examine consequentiality between student-teacher dependency and the pandemic s sequels in Saida Algeria The post- covid phase overlapping effects have switched notions beliefs and practices orbiting around independency in learning The present study captures issues underlying dependency To fulfil its intent a qualitative method was used Both questionnaire and interview were addressed to master two populations specialized in the field of didactics and the other promotion specialized in literature and civilization The findings suggest that they are entirely dependent students and that predominantly extrinsically motivated They conceive the teacher as the single boosting agent in learning And that all of them apprehend the notion independency
Keywords: student’s teacher-dependency; post-pandemic; legacy; learning process